Epidemiology, clinical profile and outcome of acute kidney injury in intensive coronary care unit - ., Sharanabasappa; Mathur, Kartikeya; Sangapur, Shivakanth M.; Meena, Baldev (International Journal of Clinical Trials, 2023)
Background: The incidence of AKI in cardiac ICU is attributed mainly to Heart Failure and Acute Coronary Syndrome. AKI occurs commonly in the setting of AHF, and is termed CRS type 1. Biomarkers and bioelectrical impedance analysis can be helpful in estimating the real volume overload and may be useful to predict and avoid AKI. The role of UF remains controversial, and it is currently recommended only for diuretic-resistant patients. Objective of current study was to study demographic & clinical profile and outcome of patients with AKI in intensive coronary care unit. Methods: This prospective study was conducted in ICCU of R.N.T. Medical College, Udaipur. All the patients with increase in serum creatinine >50% were included in the study. Detailed investigations like urinary analysis, renal function tests (blood urea, serum creatinine, serum electrolytes), USG whole abdomen, 12 lead ECG, Echocardiography and Troponin T. Results: Among cases 56.67% had ADHF, 25% had MI, 10% had structural heart disease, 3.3% had systemic illness, 1.67% had cardiogenic shock, 1.67% were cardiac surgery associated and 1.67% had other causes of AKI. 30.0% of cases required ionotropic support while 2.5% of controls required ionotropic support. 5.0% of cases required ventilator support & renal replacement therapy while none of the controls required these. Conclusions: Patients with AKI had worse outcomes when compared to non-AKI. Mortality among cases was significantly higher than controls, 10% among cases versus only 2.5% in controls.